Productivity and profitability of garden pea (Pisum sativum) as influenced by integrated nutrient management - RAJIV RAJIV; D P SINGH; SAURABH TOMAR (The Indian Journal of Agricultural Sciences, 2022)
The field experiment was conducted at Vegetable Research Farm, Kalyanpur, Kanpur (UP) during rabi 2014-15 and 2015-16, to study the effect of integrated nutrient managementon garden pea. The experiment was laid out in randomized block design with thirteen treatments of inorganic fertilizers (NPK50:60:40 kg/ha) and integration with organic sources combinations (FYM 10.0 and 20.0 t/ha, neem cake 2.5 and 5.0 q/ha, vermicompost 2.5 and 5.0 t/ ha, press mud 5.0 and 10.0 t/ha, sewage sludge 10.0 and 20.0 t/ha and poultry manure 2.5 and 5.0 t/ha) were tested against the control. Based on 2 years pooled data, application of vermicompost @ 2.5 t/ha+ half NPK through chemical fertilizers produced significantly highest green pod yield of 8.31 t/ha and net return of ` 100470/ha. The treatment of full recommended dose of NPK through chemical fertilizers (50:60:40 kg/ha) produced green pod yield of 7.29 t/ha with net return ` 86195/ha. Return per rupee invested (` 3.46) was also higher under the treatment of application of vermicompost @ 2.5 t/ha+ half NPK through chemical fertilizers. Vermicompost and half NPK through chemical fertilizers proved to be the best treatments for enhancing productivity and profitability of garden pea under Upper Gangetic Plains of Uttar Pradesh. Therefore, the practice of vermicompost integration with half dose of chemical fertilizers may serve as alternative of NPK inorganic fertilizers and fear of pollution hazards and may also be recommended to exploit the better eco-friendly economic pod yield of garden pea.